Body image and extreme attitudes toward weight in Brazilian schoolchildren (PeNSE 2012) - Rafael Moreira Claro; Maria Aline Siqueira Santos; Maryane Oliveira-Campos (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
INTRODUCTION: Adolescence is a period characterized by changes such as accelerated physical growth and sexual development. Besides having to deal with these changes, adolescents are faced with beauty standards and extreme valorization of physical appearance. OBJECTIVE: This article aims to describe body image and the practice of extreme attitudes regarding weight in Brazilian students. METHODS: Data from the National Survey of School Health (PeNSE) 2012 were used in this study. PeNSE 2012 has a representative sample of students in the 9th grade of elementary school in public and private schools across the country. A self-administered questionnaire on body image, practice of extreme measures in relation to weight and sociodemographic data was used. Body image and the practice of extreme attitudes were described for the total sample and according to gender. Poisson regression analyzes were used to identify differences in the practices of extreme attitudes between the different types of body image. RESULTS: More than 38% of the adolescents did not consider their body image as normal. Over 15% of the students referred to carry out extreme weight control practices, combining practices to loose and gain weight. Adolescents who considered themselves fat presented frequency of extreme practices for weight loss 92% higher than that shown by individuals who considered themselves normal. Similarly, adolescents who considered themselves thin presented frequency of extreme attitudes to gain weight (9.7%) higher than that shown by students who considered themselves normal (5.6%). CONCLUSIONS: The high frequency of extreme weight control practices among Brazilian adolescents is alarming and should be subject of measures in health and education fields.